2019
DOI: 10.1016/j.tate.2019.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Teaching content in practice: Investigating rehearsals of social studies discussions

Abstract: Despite evidence of its benefits, discussion remains rare in history/social science classrooms. To address this problem, communities of teacher educators (TEs) have begun supporting novices to approximate discussion facilitation. Some scholars are concerned that this turn to practice will come at the cost of content preparation. Focusing specifically on rehearsals of discussion facilitation in three history/social science methods courses, our analysis investigates whether, how, and in what ways TEs worked on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Students who made a drawing reported higher situational interest than students who wrote a text. Studies such as those of Kavanagh et al ( 2019 ) have shown the benefits of introducing discussion and debates in the classroom, both for the procedures of history and for the understanding of specific content. These international studies are showing the need to change the methodology in the classroom.…”
Section: Discussionmentioning
confidence: 99%
“…Students who made a drawing reported higher situational interest than students who wrote a text. Studies such as those of Kavanagh et al ( 2019 ) have shown the benefits of introducing discussion and debates in the classroom, both for the procedures of history and for the understanding of specific content. These international studies are showing the need to change the methodology in the classroom.…”
Section: Discussionmentioning
confidence: 99%
“…Also, cultural excursions with artists and writers were organized. That is, based on the literature (Kavanagh et al, 2019), it should be noted that lecturers have to independently choose such methods, forms and tools that they believe will help students develop their aesthetic culture, spirituality, aesthetic taste, creativity, etc. In this area, various educational activities of aesthetic orientation were of great importance, conducted by lecturers, supervisors, mentors at the student dormitory, namely: Student's Day, Culture of Communication in the Dormitory, Respect your Roommates, Exterior Appearance and Culture of Behavior, a contest for the best dormitory room.…”
Section: Discussionmentioning
confidence: 99%
“…These approximations range in authenticity, from low stakes opportunities in the classroom to formal assignments in their teaching placements. In their study of TC approximations of social studies discussions in methods courses, Kavanagh et al (2019) highlighted the potential of rehearsals to combine content learning with opportunities for TCs to try out instructional practices. This was a main goal of our morning meeting assignment.…”
Section: Guiding Theory To Support Practicementioning
confidence: 99%